Gender in Computer-Mediated Communication: An Examination of JESSE, the Library/Information Science Education Forum Electronic Discussion List - Sierpe, Eino (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Rejecting technological determinism which is largely preoccupied with the effects of technology on society, gender scholars argue that social structures play an important role in the development and diffusion of technology as well as in technological practice. They also argue that technology is a multi-faceted construct and that gender is implicated in all facets. As part of a larger investigation. .